Perancangan Sistem Informasi Penjualan pada Galeri Ulos Sianipar dan UKM Bersama Berbasis Web - Manalu, Febrianisa Mutiara; Jamaluddin, Jamaluddin; Parangin-angin, Resianta (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Information systems are a collection of sub-systems that are connected and work together in producing certain information by relying on technological assistance. In the field of trade, information systems can facilitate and improve the performance of a company. Ulos Sianipar Gallery is a business engaged in the sale of handicrafts such as ulos and songket, located in the city of Medan. The sales process still uses consumer transactions, and those who want to buy or see the available products can come directly to the store. Designing a sales information system at Ulos Gallery is expected to facilitate customers in getting the desired information. The design of the sales information system at the website-based Ulos gallery is carried out using the PHP programming language and uses MYSQL as a database storage. With this website-based sales information system, it is expected to make it easier for customers to get product information available and help the Sianipar ulos gallery in selling products and expanding the scope of sales online.